2021
DOI: 10.3390/diagnostics11112133
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Discrimination and Novel Oral Epithelial Dysplasia Stratification Using FTIR Imaging and Machine Learning

Abstract: The Fourier transform infrared (FTIR) imaging technique was used in a transmission model for the evaluation of twelve oral hyperkeratosis (HK), eleven oral epithelial dysplasia (OED), and eleven oral squamous cell carcinoma (OSCC) biopsy samples in the fingerprint region of 1800–950 cm−1. A series of 100 µm × 100 µm FTIR imaging areas were defined in each sample section in reference to the hematoxylin and eosin staining image of an adjacent section of the same sample. After outlier removal, signal preprocessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Although the DFIR spectral images used in this manuscript do not spatially resolve the nuclei, careful inspection of the darkfield visible images suggests nuclear features. Spectral differences at 1238 cm − 1 were used in the literature to discriminate between hyperplasia, epithelia dysplasia, and oral squamous cell carcinoma [ 18 ]. The prior, FTIR microscopy, study found that the average spectral intensity at 1240 cm − 1 increased as diagnosis became more severe (hyperplasia < dysplasia < squamous cell carcinoma) [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the DFIR spectral images used in this manuscript do not spatially resolve the nuclei, careful inspection of the darkfield visible images suggests nuclear features. Spectral differences at 1238 cm − 1 were used in the literature to discriminate between hyperplasia, epithelia dysplasia, and oral squamous cell carcinoma [ 18 ]. The prior, FTIR microscopy, study found that the average spectral intensity at 1240 cm − 1 increased as diagnosis became more severe (hyperplasia < dysplasia < squamous cell carcinoma) [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…IR imaging is a powerful tool for studying the spatial variation of the biochemical and molecular structure of tissues without the need for external dyes or reagents that detect molecular patterns [ 15 , 16 ]. The bulk of prior IR spectroscopic imaging data, including for oral cancer [ 17 , 18 , 19 ], has previously been acquired using Fourier transform infrared (FT-IR) microscopy that provides full IR spectral data for all pixels imaged [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Although FT-IR microscopy provides high-dimensional data due to the large spectral bandwidth, a large portion of this bandwidth does not contain biologically relevant vibrations; for example, the “cell-silent” region from ~1900 to 2700 cm − 1 is devoid of biochemical features and increasing the number of spectral features for histopathologic classification is well-known to provide diminishing returns [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work often utilizes pixels within the same set of tissue cores during classification. 67,68 This can lead to misleading results since the machine learning algorithm may learn features that correspond to specific patient traits that are challenging to generalize beyond the current dataset. We perform training and validation on mutually exclusive patient cores, achieving robust, generalizable results that enhance scientific rigor and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The current gold standard for diagnosis of premalignant or malignant lesions is histopathological evaluation to determine the degree of severity of suspicious lesions to assess the transformation risk of oral premalignant lesions [ 13 ]. Recently, Fourier transform infrared (FTIR) imaging integrated with machine learning found biochemical differences in addition to existing histopathological diagnostic processes and provide oral cancer discrimination and a novel oral epithelial dysplasia stratification strategy identifying heterogeneity between intra-samples and inter-samples of the oral epithelium [ 14 ].…”
Section: Introductionmentioning
confidence: 99%